Pengaruh Kualitas Kerja, Fasilitas Kerja, Motivasi Kerja dan Pembagian Tugas terhadap Kinerja Pegawai Dinas Perkebunan Kabupaten Muara Enim - Darmin (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2021)
The purpose of this study was to determine, analyze and prove the effect of work quality, work facilities, work motivation and division of tasks on the performance of the employees of the Muara Enim Plantation Service. The sample in the study, namely all employees of the Plantation Service of Muara Enim Regency, totaling 60 employees, will be sampled in this study. A significant value of 0.001 <0.05 then accepts Ha and rejects Ho, which means that there is a significant influence between work quality (X1) on performance (Y). A significant value of 0.016 <0.05 then rejects Ho and accepts Ha, which means that there is a significant influence between work facilities (X2) on performance (Y). A significant value of 0.586> 0.05 then accepts Ho and rejects Ha, which means that there is no significant effect between work motivation (X3) on performance (Y). Value 0.000 <0.05 then accepting Ha and rejecting Ho, which means that there is a significant influence between the division of tasks (X4) on performance (Y). Sig value 0.000 <0.05, then Ha is accepted and Ho is rejected, which means that the quality of work (X1), work facilities (X2), work motivation (X3) and the division of tasks (X4) have a significant effect together on the performance variable (Y).